Chronic rhinosinusitis and extraesophageal reflux: Who is the candidate for antireflux treatment - Zeleník, Karol; Formánek, Martin; Matoušek, Petr; Komínek, Pavel (American journal of rhinology & allergy, 2016)
BACKGROUND: During the past decade, extraesophageal reflux (EER) has been hypothesized to be one of the possible factors that contribute to the worsening of chronic rhinosinusitis (CRS). However, the relationship remains indeterminate due to its complexity, and it is not clear whether antireflux treatment is indicated for patients with recurrent CRS and who would benefit from it. OBJECTIVE: The aim of the study was to determine the severity of EER in patients with variable durations of CRS and different numbers of previous endoscopic endonasal surgeries (EES). METHODS: Ninety patients with CRS were recruited for the prospective case series. The age, sex, body mass index, reflux symptom index, duration of treatment of CRS with corticosteroids, and the number of ESS within the previous 5 years were ascertained. The severity of EER was evaluated by oropharyngeal pH monitoring by using the Restech system (the presence of EER, value of the RYAN score) and compared among the groups with varying durations of treatment of CRS (≤10 years, 11-20 years, >20 years) and different numbers of ESS within the previous 5 years (no ESS, 1-2 ESS, >2 ESS). RESULTS: Pathologic EER was present significantly more often in patients with CRS treated for >10 years (p = 0.0054) and in patients who underwent >2 ESS within the previous 5 years (p = 0.0001). CONCLUSION: Patients with CRS treated for >10 years and those who had undergone >2 ESS within the previous 5 years had significant EER. Antireflux therapy (e.g., proton pump inhibitors) can be recommended for these patients. However, its effect has to be confirmed in further studies.
Keywords: Follow-Up Studies; prospektivní studie; sinusitida; Chronic Disease; Humans; lidé; chronická nemoc; následné studie; endoskopie; gastroezofageální reflux; lidé středního věku; Disease Progression; Gastroesophageal Reflux; progrese nemoci; Middle Aged; Female; Male; Prospective Studies; Adult; Rhinitis; Rhinoplasty; rinoplastika; mužské pohlaví; Proton Pump Inhibitors; ženské pohlaví; inhibitory protonové pumpy; Endoscopy; Sinusitis; dospělí; rýma